Antioxidant Activity Test of 2,6-bis-(2Ã¢â¬â¢-furilidyn)-Cyclohexanone, ; 2,5-bis-(2Ã¢â¬â¢-furilidyn)-Cyclopentanone; 1,5-Difuryl-1,4-pentadien-3-one - Rahmawati, Ismi; Rejeki, Endang Sri; Sardjiman, . (Indonesian Journal of Cancer Chemoprevention, 2010)
Antioxidant is an essential compound to keep manÃ¢â¬â¢s health due to its function as radical scavenging. Curcumin analogÃÂ  compounds can function as antioxidant (Sardjiman, 2000). The aim of the experiment was to find out the antioxidant activity of 2,.6-bis-(2Ã¢â¬â¢-furilidin)-cyclohexanone, 2,.5-bis-(2Ã¢â¬â¢furilidin)-cyclopentanone, and 1,.5-difuril-1.4-pentadien-3-one compounds, and the antioxidant activity of each compound against DPPHÃÂ  radical with IC50 parameter as well as the correlation of compounds structureÃ¢â¬â¢s activities against antioxidant.ÃÂ  The antioxidant activity of curcumin analog compounds wereas tested against DPPH freeÃÂ  radical. The test was conducted in 5 series of concentrations by adding 4.0ÃÂ  ml test solutions with 1.0 ml DPPH. The antioxidant activity against free radical was measured usingwith spectrophotometer at 517 nm wavelength and determined for the IC50 value. The experiment employed rutin as positive control. The result of the experiment showed that curcumin analog compounds have antioxidantÃÂ  activity with IC50 of rutin, 2,.6-bis-(2Ã¢â¬â¢-furilidin)-cyclohexanone, 2,.5-bis-(2Ã¢â¬â¢furilidin)-cyclopentanone, and 1,.5-difuril-1.4-pentadien-3-one as follows: 4.93 ppm, 22.73 ppm, 20.67 ppm, and 18.80 ppmÃÂ  respectively. The highest antioxidant activity belonged toÃÂ  1,.5-difuril-1.4-pentadien-3-one compound which is 18.80 ppm . Correlation of activity structure of the 3 compounds can be seen from the log p parameter and energy space of HOMO-LUMO.ÃÂ